ATHEROSCLEROSIS - G.K. Qayumova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article deals with Atherosclerosis disease, diseases of internal organs related to it, non-modifiable risk factors, modifiable risk factors, pathological anatomy, degrees of the disease, stages of severe and mild course.